Factors Affecting the State of Empowerment of Migrant Workers through Complaint Mechanisms: Comparative Study of Migrant Workers in Thailand and Japan (Global Journal of Human-Social Science, 2015)
Migrant workers one of vulnerable worker population are likely to live and spend their lives in poverty an expose to limited chances and options This study aims to identify factors affecting different state of empowerment using migrant workers decisions to promptly respond to labour-related problems as a proxy This study uses a quantitative approach Multinomial Logistic Model as well as a qualitative approach an analysis of interviews The study applies Thailand and Japan as developing and developed countries where sharing same characteristics as net immigrant countries in East and South East Asia During 2013-2015 a total of 150 migrant workers 75 migrants in Thailand and 75 migrants in Japan were interviewed with the focus on low-skilled migrant workers Though the characteristics of migrant workers in these two countries are generally different factors affecting migrant workers being in the state of empowerment are indifferent The result of the regression suggests that an additional year of schooling and holding a proper working permit increase the probability to be empowered It is clear that those who know what to do but take no action consider themselves having alternative options The current scheme in promoting labour rights should not only outreach and disseminate about complaint mechanisms to migrant workers but also emphasize on the effectiveness of the mechanisms and labour market analyses Promoting the accessibility of migrant workers to Information and Communication Technology is also a key to better understanding in labour rights widening their job options in countries of destination and their home country though an easy and timely accessibility and escalating their skills to ensure their better job options and better individual bargaining power with their employers
Keywords: Complaints mechanisms; empowerment; migrant workers